The Influence of E-Recruitment and Job Characteristics on Job Application Interest with Corporate Reputation as a Mediating Variable - Farida, Ida; Wardhana, Ery Tri Djatmika Rudijanto Wahju; Churiyah, Madziatul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the influence of e-recruitment and job characteristics on job application interest, with company reputation serving as a mediating variable. The research addresses a gap identified in previous studies. A quantitative approach was adopted, using non-probability sampling with purposive sampling methods. Data was collected through questionnaires distributed to respondents, using a 5-point Likert scale. The sample consisted of 380 respondents, and data analysis was conducted using the SmartPLS (Partial Least Squares) software. The findings indicate that both e-recruitment and job characteristics have a positive and significant effect on job application interest. Additionally, e-recruitment and job characteristics positively and significantly impact company reputation. Company reputation was found to directly mediate the relationship between job characteristics and job application interest positively and significantly. However, it was unable to mediate the direct relationship between e-recruitment and job application interest.